A new era of cancer immunotherapy: vaccines and miRNAs - Gitika Sareen; Maneesh Mohan; Ashi Mannan; Kamal Dua; Thakur Gurjeet Singh (Cancer Immunology, Immunotherapy)
Abstract Cancer immunotherapy has transformed the treatment landscape, introducing new strategies to fight various types of cancer. This review examines the important role of vaccines in cancer therapy, focusing on recent advancements such as dendritic cell vaccines, mRNA vaccines, and viral vector-based approaches. The relationship between cancer and the immune system highlights the importance of vaccines as therapeutic tools. The discussion covers tumor cell and dendritic cell vaccines, protein/peptide vaccines, and nucleic acid vaccines (including DNA, RNA, or viral vector-based), with a focus on their effectiveness and underlying mechanisms. Combination therapies that pair vaccines with immune checkpoint inhibitors, TIL therapy, and TCR/CAR-T cell therapy show promising potential, boosting antitumor responses. Additionally, the review explores the regulatory functions of microRNAs (miRNAs) in cancer development and suppression, featuring miR-21, miR-155, the let-7 family, and the miR-200 family, among others. These miRNAs influence various pathways, such as PI3K/AKT, NF-κB, and EMT regulation, providing insights into biomarker-driven therapeutic strategies. Overall, this work offers a thorough overview of vaccines in oncology and the integrative role of miRNAs, setting the stage for the next generation of cancer immunotherapies.